The current state of training specialists in scientific and innovative technologies in Kyrgyzstan’s higher education institutions (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article highlights that the training of specialists in Kyrgyzstan’s higher education institutions (HEIs) in the field of scientific and innovative technologies (particularly artificial intelligence – AI, digital technologies, robotics, and STEM – science, technology, engineering, mathematics, IT, and green technologies) is a key component of the National Development Strategy. Emphasis is placed on PhD programs, with an analysis of the system’s state as of 2025. Through the Education Development Strategy (EDS-2040) and Concept (EDC-2030), the task of strengthening research activities in HEIs and integrating AI and digital technologies into education is examined. The National Development Program until 2026 prioritizes enhancing the scientific potential of HEIs, as research is essential to ensure the relevance of knowledge. The methodology includes document analysis and statistical data. The analysis concludes that scientific and innovative technologies contribute to building a knowledge-based economy, but further deepening of reforms is necessary.
Keywords: PhD programs, science, innovation, HEIs, Erasmus , specialist training, education reforms